EKOLOGI SEMUT API (Solenopsis invicta) - Taib, Minarti (Jurnal Sainstek, 2012)
Ant (Solenopsis invicta) has the small body, social life and discipline the highest, loyal to the rule, smart and creative. Even the ant has the small body but it could hit the people and it cause a bite has liquid and swallen because it has poison and produce the poison chemistry such as acid format. The ant has role in ecosystem to hole the amound soil and it coused to pick soil up. It could live together with another living organism, so it is avoided from extinction and energy cycle on one habitat.